Traumatic granuloma/eosinophilic ulcer - Zain, R.B.; Abdul Hamid, J.; Awang, M.N. (1986)
Two case reports of an uncommon type of oral ulcerative lesion are presented. These lesions are of long duration, benign and reactive, and may clinically mimic a malignant ulcer. Histologically, these are deep lesions which exhibit 'pseudoinvasion' into skeletal muscle. There is a predominance of eosinophils while other chronic inflammatory cells such as plasma cells and histiocytes are in abundance. A brief review of the literature showed past treatment being surgical excision, incisional biopsy, radiation, cryosurgery with liquid nitrogen and no treatment. All modalities used result in resolution of the lesion.